Pe Penafsiran Ekstensif Atas Tindak Pidana Korupsi Sebagai Perbuatan Mengkhianati Negara : Tindak Pidana Korupsi - Sari, Wulan (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2024)
Indonesia is a unitary state based on law. Almost all arrangements in the state are governed by law, not politics or economics. This is the concept of the rule of law (rechstaat) in a country. As a state of law, the rules used become an important part of the state process, including the spirit of loyalty and nationalism. Quoted from Britannica, loyalty is a general term that indicates a person's devotion to a particular object, loyalty is a loyal nature that is manifested in various forms of action. In various cases, it shows that there are many who commit treason against the country, this is evidenced by the increasingly damaged moral of the nation who no longer care about the importance of Pancasila in the life of the nation and state. Conditions like this are very worrying, so it greatly affects the condition of the country which leads to injustice. The problems that will be discussed in this study are: (1) How is Corruption as a Special Crime in Indonesia (2) How is the Extensive Interpretation of the Crime of Corruption as an Act of Betraying the State as Article 6 of the 1945 Constitution of the Republic of Indonesia Chapter III on Power.